Analysis of early experiments with land redistribution in South Africa : case of Vhembe District Municipality of Limpopo Province - Mukovhe, N.; Moyo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
The aim of the paper is to examine the perceptions of communities in the Vhembe District on their experiences on redistribution models. The District experienced the transition from households-based and poverty-oriented Settlement Land Acquisition Grant (SLAG) model to the commercial-oriented Land Redistribution for Agricultural Development (LRAD) to the current Proactive Land Acquisition Strategy (PLAS). All three models were based on the 'willing seller- willing buyer' principle, which is widely seen as one of the major reasons for the slow pace of land reform. Its objectives are to assess the effect of the 'willing seller, willing buyer' principle on the pace of land redistribution in the area; to analyse the rationale for the shifts in policy over type of redistribution model and their implications on ownership and control of and to examine the implementation and subsequent effects of the redistribution approaches on the livelihoods of the farming communities. The research design was qualitative and specifically case studies of each model. Key findings included limited impact of land redistribution on livelihoods of the farmers, inadequate technical, financial and other material support and dissatisfaction of farmers under the PLAS model on lack of title deeds as government opted for a leasing the land instead. The paper recommends more comprehensive research on the pertinent issues of individual property rights/title to land as opposed to state ownership/leasing approach that characterizes the PLAS model.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Commercialisation; Land redistribution; Leasing; Private property rights; Sustainability; Land reform -- South Africa -- Limpopo; Land tenure -- South Africa -- Limpopo